An Approach for Determining an Index for Lightness-Darkness Attribute of Shadows in Artificial Lit Spaces. Issue 3 (3rd July 2022) - Akbay Çelikmez, Selcen; Öztürk, Leyla Dokuzer
ABSTRACT: Shadows, modelling, and directional lighting are lighting criteria which are closely related with each other. Shadows have two attributes, namely harshness-softness and lightness-darkness. Both attributes can be examined in two respects that is self-shadow and cast-shadow. A shadow with sharp edges is harsh shadow, while a shadow with blurred edges is soft shadow. The size of the luminaire determines whether the edges of a shadow are sharp or blur. The contrast between the illuminated and the shaded areas determines the lightness-darkness of shadows. If this contrast is weak the shadow is perceived as light, while a strong contrast causes the shadow to be perceived as dark. The observer is often unable to distinguish the effects of two different shadow attributes from each other and judges the appearance of objects or faces as a whole as pleasant or not. However, the two properties of shadows can be defined independently from each other and considered separately as lighting design criteria. Directional lighting is used when the texture and shape of objects or people are to be revealed or emphasized. Finally, it can be said that modelling describes the general appearance of objects and people and involves both the shadow properties and the effects of directional lighting. The aim of this study is to define an index with regard to the lightness-darkness attribute of shadows. The approach developed in this respect is applied for both cast- and self-shadows. The acceptable limits for both indexes are determined based on the main types of luminaires that are often installed in a room. The introduced lightness-darkness indexes with their limit values can be considered as lighting design criteria.